Speaking in English: Oral Communication Apprehension and Self-Perceived Communication Competence among Marketing UndergraduatesinMalaysia - Siti Haslina, Hussin; Andi Noraisya, Makmur (Human Behavior, Development and Society, 2021)
In this study perceptions of final year marketing undergraduateswere investigatedat Universiti Malaysia Sarawak towards the feeling of anxiety they experienced when speaking in English. Specifically, the objectives of the study were to determine (a) the level of oral communication apprehension; (b) the level of self–perceived communication competence; and (c) to identify the relationship between the students’ English oral communication apprehension and self-perceived communication competence. A quantitative research design was adopted and McCroskey’s well-known questionnairewas used to measure communication apprehension levels in four communication contexts (groupdiscussion, meeting, interpersonal and public speaking).TheSelf-Perceived Communication Competencequestionnaire by the McCroskeys’ was used to measure communication in various contexts(public, meeting, group, and dyad) and from different receivers (stranger, acquaintance and friend). The results showed that the final year marketing undergraduateshad moderate levels of oral communication apprehension. Their level of self-perceived communication competence was also at the moderate level. Results also indicated a significant correlation between communication apprehension and self-perceived communication competence among the students. Keywords:Oral communication apprehension, self-perceived competence, marketing undergraduates